How do you evaluate the limit (sqrt(x+1)-2)/(x^2-9) as x approaches -3?

Since sqrt(x+1) is not defined at x=-3, we will take limit as x approaches +3 instead of -3

1 Answer
Aug 22, 2016

1/24.

Explanation:

Reqd. Limit=lim_(xrarr 3) (sqrt(x+1)-2)/(x^2-9)

=lim_(xrarr 3) (sqrt(x+1)-2)/(x^2-9)xx(sqrt(x+1)+2)/(sqrt(x+1)+2)

=lim_(xrarr 3) (x+1-4)/((x+3)(x-3)(sqrt(x+1)+2))

=lim_(xrarr 3) cancel((x-3))/((x+3)cancel((x-3))(sqrt(x+1)+2))

=lim_(xrarr 3) 1/(x+3)xx1/(sqrt(x+1)+2)

=(1/6)(1/4)

=1/24.